Experimental Study on Thermal Regime and Frost Jacking of Pile Foundation During Operation Period in Permafrost Regions - Shang, Yunhu; Niu, Fujun; Fang, Jianhong; Wu, Libo (Frontiers in Earth Science, 2022)
The stability of a cast-in-place pile foundation in permafrost region is primarily subject to the thermal regime and tangential frost-heave forces (TFF) during the operation period. However, studies focusing on the thermal and mechanical characteristics of pile foundation during runtime are rare. To investigate the effect of pile foundation on the thermal regime and quantify the magnitude of unit tangential frost-heave forces (UTFF), a field experiment was conducted on the Qinghai–Tibet Plateau, China. Results showed that the cast-in-place pile foundation enhanced the heat exchange between the atmosphere and soil, which expanded the annual range of the surrounding ground temperature. Furthermore, the permafrost table depth was increased by 0.4–0.7 m (0.33–0.58 times the pile diameter). The TFF increased significantly when the soil temperature decreased from 0 °C to -0.5 °C. Meanwhile, the thickness of the frost heaving layer was approximately double that of the active layer, in which the maximum UTFF was higher than 52.04 kPa. The adfreezing bond force of permafrost to pile shaft burdened most of the applied load, and the end bearing contributed relatively little. Findings from this study will benefit the stability maintenance and structure design of pile foundation in permafrost regions.